Developing a pollution free environment framework through technology Integration (e-Hailing App) - Sham, Rohana; Amir Hussin, Amir 'Aatieff; Abdamia, Noranita; Mohd Anuar, Marhani (e-IPH Ltd., 2019)
Cleaning the polluted river involves a considerable cost. For Baram and Miri river in Sarawak, the problem had become worst due to rapid growth. Thus, e -hailing app is proposed to reduce the problem faced. This paper will examine on the important features of the app and major function where towards the end, river pollution can be kept low with full engagement from the society. This design is in line with the 11th sustainable goals to reduce pollution. Thus, major outcome is to produce the app to reduce the amount of pollution surrounding the river in promoting a quality living.